Implementasi Model Pembelajaran Contextual Teaching & Learning Untuk Meningkatkan Social Skill Peserta Didik Pada Mata Pelajaran PAI Kelas VII SMP Negeri 2 Karangkobar Banjarnegara - Prihatin Nurul Fitriah; Rifqi Muntaqo; Ali Imron (STIKes Ibnu Sina Ajibarang, 2024)
Social skills are an important part of a humans ability to live, because social skills are very much needed in social life. Social skills are skills in interacting, communicating and collaborating with another people. Social skills also can be learned and developed through the learning process. With the increasing of social problems that occur, social skills are a very important skill to have. The aim of this research is to get an overview and analyze the development of students social skill levels through the implementation of the contextual teaching & learrning (CTL) model in Islamic Religius Education subjects. This research uses a qualitative field approach. The research location taken was SMP Negeri 2 Karangkobar Banjarnegara. The data sources used are primary data and secondary data. Primary data includes the results of interviews and observations. Meanwhile, secondary data is obtained from documentation results. Using three data collection techniques, namely interview, observations, and documentation. Analyzing data is carried out in three stages: data reduction, data presentation, and drawing conclusion. The conclusion of this research is that trhough the use of the contextual teaching & learning model, students social skills have increased, although not significantly. This is because forming and changing human character requires quite a long process and time. However, by consistently and always developing the CTL learning model that is carried out, it is hoped that it will be able to help teachers in their efforts to improve social skills. Therefore, the use of the CTL model is considered effective in helping teachers in efforts to improve students social skills.